2013
DOI: 10.4081/jphr.2013.e15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge and Practice Behaviours of a Group of Iranian Obstetricians, General Practitioners, and Midwives, Regarding Periodontal Disease and its Effect on the Pregnancy Outcome

Abstract: BackgroundPeriodontal disease is considered as a risk factor for poor pregnancy outcomes, including preterm birth and low birth weight. Only few studies have assessed the knowledge and practice behaviours of healthcare providers, concerning oral health during pregnancy, periodontal diseases and their role in adverse pregnancy outcomes. The present study aimed to compare the knowledge and practice behaviours of a group of Iranian obstetricians, general practitioners, and midwives about periodontal disease.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
6
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
1
9
6
3
Order By: Relevance
“…In the same line, the results of a study performed by Golkari et al indicated that gynecologists obtained higher scores regarding knowledge, compared to midwives and general physicians, and due to improper education, midwives had an insufficient level of knowledge (21). The results of the mentioned study were not consistent with those of the present study, and the participants in the current study obtained higher levels of knowledge.…”
Section: Table1) Demographic Characteristics Of Dentists and Gynecolocontrasting
confidence: 97%
“…In the same line, the results of a study performed by Golkari et al indicated that gynecologists obtained higher scores regarding knowledge, compared to midwives and general physicians, and due to improper education, midwives had an insufficient level of knowledge (21). The results of the mentioned study were not consistent with those of the present study, and the participants in the current study obtained higher levels of knowledge.…”
Section: Table1) Demographic Characteristics Of Dentists and Gynecolocontrasting
confidence: 97%
“…This confirmed similar findings of preliminary research conducted in NSW [ 39 ]. The knowledge deficits of nurses and midwives do not appear to be unique to Australian education programs and have been reported internationally for example in Norway, North Carolina and Iran [ 47 , 51 , 52 ]. Victorian study participants were very receptive to the MIOH program and discussed the immense gains in knowledge of the implications of poor oral health for pregnant women that they received from participating in the education program.…”
Section: Discussionmentioning
confidence: 99%
“…Bidan dan dokter spesialis kandungan sebagai penyedia pelayanan kesehatan yang paling banyak dikunjungi oleh ibu hamil dapat membantu meningkatkan angka pemanfaatan pelayanan kesehatan gigi mulut selama kehamilan. 12 Penting untuk penyedia layanan kesehatan ini menyadari risiko penyakit periodontal dan hubungannya dengan hasil kehamilan yang buruk. 12 Hasil Analisis Bivariat menunjukkan bahwa terdapat hubungan yang bermakna antara keluhan atau masalah kesehatan gigi mulut ibu hamil dengan pengetahuan kesehatan gigi mulut ibu hamil di wilayah kerja Puskesmas Serpong.…”
Section: Pembahasanunclassified
“…12 Penting untuk penyedia layanan kesehatan ini menyadari risiko penyakit periodontal dan hubungannya dengan hasil kehamilan yang buruk. 12 Hasil Analisis Bivariat menunjukkan bahwa terdapat hubungan yang bermakna antara keluhan atau masalah kesehatan gigi mulut ibu hamil dengan pengetahuan kesehatan gigi mulut ibu hamil di wilayah kerja Puskesmas Serpong. Sebuah korelasi positif juga ditemukan pada penelitian di Polandia dimana Ibu hamil dengan pengetahuan kesehatan gigi mulut yang memadai, tidak memiliki masalah atau keluhan mengenai kesehatan gigi mulut mereka.…”
Section: Pembahasanunclassified
See 1 more Smart Citation